IMPLEMENTASI SISTEM INFORMASI AKUNTANSI JURNAL.ID DI PT DOI MASAHARU SONODA PILATES - Agustina Gita Maharani, (2023)
Through this Final Project, the author aims to study and examine the implementation of Jurnal.id accounting information system at PT Doi Masaharu Sonoda Pilates. The specific objective of this Final Project is to fulfill one of the requirements for the completion of the Diploma Three (DIII) program in the Accounting department at the Universitas Pembangunan Nasional Veteran Jakarta. An accounting information system is a system used to collect, process, and present financial information accurately and timely to support business decision-making. In this final project, Jurnal.id serves as the accounting information system implemented at PT Doi Masaharu Sonoda Pilates. Jurnal.id is a popular accounting software that assists companies in managing accounting processes such as transaction recording, financial report preparation, and tax reporting more efficiently. Additionally, Jurnal.id offers features that facilitate integration with other systems, such as Zahir, another accounting software already used by the parent company. Through this final project, it is expected to identify the benefits and challenges of implementing the Jurnal.id accounting information system at PT Doi Masaharu Sonoda Pilates, as well as contribute to the understanding of the application of accounting information system in the real-world business context.